Non-target Site Tolerance Mechanisms Describe Tolerance to Glyphosate in Avena sterilis - Fernández-Moreno, Pablo T.; Alcantara-de la Cruz, Ricardo; Cruz-Hipólito, Hugo E.; Rojano-Delgado, Antonia M.; Travlos, Ilias; De Prado, Rafael (Frontiers in Plant Science, 2016)
Sterile wild oat (Avena sterilis L.) is an autogamous grass established in warm climate regions. This species has been used as a cover crop in Mediterranean perennial crops during the spring period prior to initiating competition with the main crop for water and nutrients. However, such cover crops need to be controlled (by glyphosate or tillage) before the beginning of summer period (due to the possibility of intense drought stress). In 2011, the olive grove farmers of southern Spain expressed dissatisfaction because of the ineffective control with glyphosate on A. sterilis. Experiments were conducted to determine whether the continued use of glyphosate over a 5 year period had selected a new resistant or tolerant species. The GR50 values obtained for A. sterilis were 297.12 and 245.23 g ae ha-1 for exposed (E) and un-exposed (UE) glyphosate accessions, respectively. The spray retention and shikimic acid accumulation exhibited a non-significant difference between the two accessions. The results of 14C- glyphosate absorption was the same in the two accessions (E and UE), while the translocation from the treated leaf to the rest of the shoots and roots was similar in A. sterilis accessions. Glyphosate metabolism to aminomethylphosphonic acid (AMPA) and glyoxylate was similar in both accessions, but increased after treatment with glyphosate, indicating that metabolism plays an important role in tolerance. Both A. sterilis accessions, present similarity in the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) activity enzyme with different glyphosate concentrations and without glyphosate, confirming that both accessions present the same genomic characteristics. The above-mentioned results indicate that innate tolerance to glyphosate in A. sterilis is probably and partly due to reduced herbicide absorption and translocation and metabolism compared to the susceptibility of other grasses weeds like Chloris inflata, Eleusine indica and Lolium rigidum.